2014
DOI: 10.1016/j.eururo.2013.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported Outcomes in Randomised Controlled Trials of Prostate Cancer: Methodological Quality and Impact on Clinical Decision Making

Abstract: Context Patient-reported outcomes (PRO) data from randomised controlled trials (RCTs) are increasingly used to inform patient-centred care as well as clinical and health policy decisions. Objective The main objective of this study was to investigate the methodological quality of PRO assessment in RCTs of prostate cancer (PCa) and to estimate the likely impact of these studies on clinical decision making. Evidence acquisition A systematic literature search of studies was undertaken on main electronic databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
73
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 37 publications
7
73
3
1
Order By: Relevance
“…Similar to past reviews [19,21,23], we found that reporting of PRO endpoints in a dedicated publication was a predictor of more complete reporting. Whilst detailed secondary PRO publications should be encouraged as they allow for presentation of additional analyses, the principal PRO findings should be reported in accordance with CONSORT-PRO and in the main RCT publication to facilitate interpretation of PRO results within the context of other endpoints, and to provide the patients' perspective to complement other trial information.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Similar to past reviews [19,21,23], we found that reporting of PRO endpoints in a dedicated publication was a predictor of more complete reporting. Whilst detailed secondary PRO publications should be encouraged as they allow for presentation of additional analyses, the principal PRO findings should be reported in accordance with CONSORT-PRO and in the main RCT publication to facilitate interpretation of PRO results within the context of other endpoints, and to provide the patients' perspective to complement other trial information.…”
Section: Discussionsupporting
confidence: 85%
“…Again, these are knowledge transfer concerns requiring intervention to improve reporting practices and to ensure PRO results are interpreted accurately so they can appropriately inform patient care. Recent reviews confirm that reporting of PRO endpoints remains unsatisfactory overall; particularly regarding the reporting of PRO hypotheses, methodology, missing data, and generalisability of results [19][20][21][22][23][24][25][26]. Failing to report this information is wasteful as it limits the potential for readers to appraise the effect of interventions on patient health status, and the potential for PRO systematic reviews to impact clinical recommendations and health policy [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key trend in US health care has been more focus on patient-reported outcomes (PROs), reflecting those aspects of outcome that are best obtained directly from patients, such as functional, psychosocial, and healthrelated quality of life. Importantly, PROs represent a metric applicable across varying procedures and provider types and, applied with quality-adjusted life-year data, enable comparative, effective research studies that inform valuebased health care models.So, how are we doing with collecting PRO data in prostate cancer (PCa) management?During the past decade, >22 000 PCa patients have been enrolled in 65 clinical trials with a PRO component [2]. Approximately 48% of these patients studied had localized PCa.…”
mentioning
confidence: 99%
“…During the past decade, >22 000 PCa patients have been enrolled in 65 clinical trials with a PRO component [2]. Approximately 48% of these patients studied had localized PCa.…”
mentioning
confidence: 99%